2019
DOI: 10.1186/s12935-019-1037-1
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-resistant A549 non-small cell lung cancer cells can be identified by increased mitochondrial mass and are sensitive to pemetrexed treatment

Abstract: BackgroundCisplatin plus pemetrexed combination therapy is considered the standard treatment for patients with advanced, non-squamous, non-small-cell lung cancer (NSCLC). However, advanced NSCLC has a 5-year survival rate of below 10%, which is mainly due to therapy resistance. We previously showed that the NSCLC cell line A549 harbors different subpopulations including a mesenchymal-like subpopulation characterized by increased chemo- and radiotherapy resistance. Recently, therapy resistance in hematological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…In detail, targeting mitochondrial energetics and metabolism overcame drug resistance in acute myeloid leukemia (AML) [ 15 , 16 ]. In lung cancer, high mitochondrial activity is related to chemotherapy resistance [ 17 , 18 ]. Thus, aberrant mitochondrial metabolism might prove to be the Achilles heel of chemotherapy-resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, targeting mitochondrial energetics and metabolism overcame drug resistance in acute myeloid leukemia (AML) [ 15 , 16 ]. In lung cancer, high mitochondrial activity is related to chemotherapy resistance [ 17 , 18 ]. Thus, aberrant mitochondrial metabolism might prove to be the Achilles heel of chemotherapy-resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In replicating cancer cells, blocked thymidine synthesis leads to nucleotide pool imbalance, which subsequently leads to DNA replication errors and activation of the DNA damage response machinery, and, if not repaired, to cell death (reviewed in [ 28 ]). Indeed, we previously showed that blocking nucleotide synthesis by MTA treatment results in the accumulation of persistent DNA damage [ 18 , 29 ]. Further, we found that prolonged pretreatment with MTA enhances the anticancer efficacy of subsequent cisplatin treatment [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stained cells were analyzed by flow cytometry (Attune cytometry, BD biosciences). Cisplatin 80 μM was used as a positive control [32,33].…”
Section: Active Caspase 3 Assaymentioning
confidence: 99%
“…We utilized the well-established SRB cell viability assay [4,5] to determine the inhibitory effect of RO 48-8071 on drug-resistant colon, lung and pancreatic cells of aggressive nature [6][7][8][9][10][11][12]. The SRB assay quantitates protein content of surviving cells as an index of cell growth and viability, as described in our previous publications [1,2,13].…”
Section: Cell Viability Assaymentioning
confidence: 99%